Pengaruh Price To Book Value (PBV), Debt To Equity Ratio (DER), Return on Assets (ROA) Terhadap Price Earning Ratio (PER) pada Perusahaan Sub Sektor Plastik dan Kemasan Yang Terdaftar di Bursa Efek Indonesia - Marissa Putriana (J-MAS (Jurnal Manajemen dan Sains), 2019)
This research aims to obtain empirical evidence regarding the influence of Price to Book Value (PBV), Debt to Equity Ratio(DER), Return on assets (ROA) against the Price Earning Ratio. (PER)  The data used are secondary data in the form of the financial statements the company sub sectors of plastics and packaging listed in indonesia stock exchange period 2015-2017. The sample used as 6 companies, withdrawing a sample using the method of purposive sampling. Analytical techniques used was multiple linear regression. The results showed that (1) the Price to Book Value, Debt to Equity Ratio, Return on assets simultaneously effect significantly to Price Earning Ratio (2) Price to Book Value and Return on assets partially effect significantly to Price Earning Ratio, while Debt to Equity Ratio partially do not affect significantly to Price Earning Ratio. Based on  results of testing the coefficient of determination R square value was known to 0.703.  Meaning of 70.3% Price Earning Ratio variable can be explained by Price to Book Value, Debt to Equity Ratio and Return on assets, while the remaining 29.7% are affected by other variables outside of this research.